Evaluation of prevalence of anxiety and depression among glaucoma patient with delay in care due to covid-19 pandemic in Kelantan using hospital anxiety and depression scale questionnaire. - Abidin, Nuratiqah Zainal (2023)
INTRODUCTION Glaucoma is the leading cause of irreversible blindness worldwide with primary open angle glaucoma (POAG) as the predominant subtype followed by primary angle closure glaucoma (PACG). Previous studies conducted before have shown that the level of depression and anxiety among glaucoma patient is higher compared to normal population because it had affected their quality of life. On the other hand, severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) pandemic had changed global healthcare delivery after World Health Organization (WHO) had declared it a Public Health Emergency of International Concern on January 30, 2020 and a pandemic on March 18, 2020. The Malaysian government has enforced a lockdown or Movement Control Order (MCO) that limits people's movement in and out of an area in order to prevent the spread of COVID-19. As a result, treatment has been delayed and individuals with chronic conditions such as glaucoma patients have become increasingly anxious and concerned about the potential risk of losing their eyesight. OBJECTIVE To evaluate the prevalence of anxiety, depression, and its associated factors among glaucoma patients with delay in care due to the COVID-19 pandemic in Kelantan using the Hospital Anxiety and Depression Scale (HADS) Malay version. METHODOLOGY This cross-sectional study was conducted between January 2021 and June 2022 among 160 glaucoma patients who attended the Ophthalmology Clinic, Hospital Raja Perempuan Zainab II, Kelantan, and Ophthalmology Clinic, Hospital Universiti Sains Malaysia. All types of glaucoma patients aged between 40 to 80 years old without psychiatry problems, deaf or hearing impairment, and other ocular comorbidities were included in this study. Eligible patients underwent visual acuity assessment, complete ocular examinations, and fundus evaluation via slit lamp biomicroscope. Detailed demographic data with ocular and systemic history were taken. The Malay version of HADS questionnaire was read out to glaucoma patients. Pearson chi-square test and Fisher exact test were used to identify the associated factors associated with anxiety and depression. RESULTS One hundred and sixty patients were included in the study. Eighty-two were men (51.2%) and 78 (48.8%) were women. The mean age of the patients was 65.70 years. One hundred and thirty-three (82.1%) were Malay patients and 129 patients had comorbidities (80.6%). The prevalence of anxiety and depression due to delay in care among our glaucoma patients was 11.3 % and 13.1% respectively. Both anxiety and depression were associated with laterality (P = 0.001, P < 0.001), number of antiglaucoma (P = 0.01, P = 0.010), and no family history of glaucoma (P = 0.019, P = 0.003). CONCLUSION Glaucoma patients with bilateral disease and those who require a higher number of antiglaucoma treatments experience more anxiety and depression during the COVID-19 pandemic and Movement Control Order (MCO), compared to those with unilateral disease and lower numbers of antiglaucoma treatments. However, our study did not find a significant association between a positive family history of glaucoma and anxiety or depression among glaucoma patients. Therefore, in the event of future pandemics or lockdowns, it is important to prioritize urgent appointments for glaucoma patients.